2023
DOI: 10.3847/1538-4357/acea5c
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Acceleration of Cosmic Rays in a High-β Medium

Alex Lazarian,
Siyao Xu

Abstract: In a weakly compressible high-β medium, pitch-angle scattering and the associated scattering acceleration of cosmic rays (CRs) by anisotropic Alfvén and slow modes of magnetohydrodynamic (MHD) turbulence is inefficient. To tap the energy from magnetic compressions for efficient particle acceleration, a diffusion mechanism that can effectively confine particles in space without causing their trapping or pitch-angle isotropization is needed. We find that the mirror diffusion in MHD turbulence recently identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…A fraction of the turbulent energy can be converted into nonthermal components such as cosmic rays and the magnetic field through stochastic acceleration and a turbulent dynamo. Turbulence in astrophysical environments may accelerate particles via different mechanisms, including resonant and nonresonant ones (e.g., Ptuskin 1988;Schlickeiser & Miller 1998;Cho & Lazarian 2006;Brunetti & Lazarian 2007;Lynn et al 2014;Lemoine 2021;Bustard & Oh 2022;Lazarian & Xu 2023). Recent MHD simulations of galaxy clusters suggested that the turbulence in the ICM is dominated by the solenoidal (incompressible) mode (e.g., Miniati 2015;Vazza et al 2017).…”
Section: Cr Reacceleration and Field Amplification By Solenoidal Turb...mentioning
confidence: 99%
“…A fraction of the turbulent energy can be converted into nonthermal components such as cosmic rays and the magnetic field through stochastic acceleration and a turbulent dynamo. Turbulence in astrophysical environments may accelerate particles via different mechanisms, including resonant and nonresonant ones (e.g., Ptuskin 1988;Schlickeiser & Miller 1998;Cho & Lazarian 2006;Brunetti & Lazarian 2007;Lynn et al 2014;Lemoine 2021;Bustard & Oh 2022;Lazarian & Xu 2023). Recent MHD simulations of galaxy clusters suggested that the turbulence in the ICM is dominated by the solenoidal (incompressible) mode (e.g., Miniati 2015;Vazza et al 2017).…”
Section: Cr Reacceleration and Field Amplification By Solenoidal Turb...mentioning
confidence: 99%